Contemporary Hospitalization Rate Among Adults With Complex Congenital Heart Disease. (May 2016) - Cedars, Ari; Benjamin, Lawrence; Vyhmeister, Ross; Harris, Kathryn; Bradley, Elisa A.; Wadia, Subeer; Awad, Ahmed J.; Novak, Eric
Background: Adults with congenital heart disease are hospitalized at increasing rates in the Western world. Identification of rates of and risk factors for hospitalization is essential for research and improving patient outcomes. Methods: We conducted a single-center retrospective analysis of patients with a primary diagnosis of tetralogy of Fallot (TOF), transposition of the great arteries (bothd - andl -transposition of the great arteries [TGAs]), or single ventricle (SV). We investigated the rates of mortality, annual hospitalization, and patient-specific risk factors for unplanned cardiac hospitalization. Results: Adult patients with complex congenital heart disease are hospitalized at a rate four to eight times greater than the general US population ( P < .001). In addition, there are significant differences between the rates of hospitalization in TOF and TGA (0.39 and 0.41 hospitalizations per patient-year, respectively) and SV (0.72 hospitalizations per patient-year). The majority of excess hospitalizations in the study group were due to cardiac disease ( P < .001 for all three groups). Risk factors for unplanned cardiac hospitalization in TOF included pulmonary atresia, depressed left ventricular and right ventricular ejection fraction, and smoking; in TGA, they included Ebstein malformation, surgeries other than primary repair, noncardiac diagnoses, atrial arrhythmias, atrioventricular nodal block, left ventricular ejection fraction, and smoking; and in SV, they included atrial arrhythmias and cyanosis. Conclusions: Patients born with complex congenital heart disease are hospitalized far more frequently than the general US population, primarily for cardiac-related illness. Future research should focus on confirming the present findings and on identification of strategies to improve outcomes in this growing group of patients.